EFISIENSI TEKNIS USAHATANI JAGUNG DI KECAMATAN REMBOKEN KABUPATEN MINAHASA - Juliana Ruth Mandei (Sam Ratulangi University, 2015)
The study was conducted in order to determine the efficiency of maize farming techniques in District Remboken and analyze the determinants of the level of technical efficiency of maize farming in the district Remboken. Sampling was done by using the method of Sampling Cluster, specifically three farmers groups program participant Integrated Crop Management Field School (SLPTT) Â and three farmers group who are not participants SLPTT. The variables measured in this study is the production (kg / season), land planted with maize (ha), amount of labor used (HOK), Total Urea is used (kg), amount of fertilizer used Phonska (kg ), amount of seed used (kg) and the amount of pesticides used (ltr). The variables used to see the factors affecting technical efficiency is age measured in years farmers, farmer education levels measured by using dummy variables, and the number of dependents of farmers. To see the technical efficiency of maize farming using frontier production function and to analyze the factors affecting technical efficiency of farming corn used multiple regression analysis with OLS. The results showed that maize production was significantly affected by labor, seeds and herbicides, Most cultivated maize farming has been technically efficient farmers and the level of technical efficiency of farmers follow SLPTT lower than farmers who do not follow SLPTT. The number of dependents and education levels significantly affect the level of technical efficiency of maize farming in the district Remboken. Necessary to reformulate the model of Integrated Crop Management Field School is more effective to improve the ability of farmers to manage their farming.